PERLINDUNGAN HUKUM PADA PASIEN TERHADAP MALPRAKTEK DOKTER - Evander Reland Butar Butar; Suteki Suteki (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
Patient is any person who consulted a physician profession regarding his or herhealth problems to get healed from his illness. Patient is king in health service. Inorder to get the case, a patient will be checked for health by a doctor who has licensedthe practice. In article 44 of Law no. 29 Year 2004 on the practice of Medical states